Faktor-faktor Yang Memengaruhi Kualitas Audit - Klara Immanuel, Giovanni; Salim, Susanto (Universitas PGRI Yogyakarta, 2024)
This research aims to explore the factors influencing an auditor's audit quality. The researcher is interested in conducting an in-depth study to examine the impact of audit tenure, auditor switching, and audit firm size on audit quality. This study is quantitative descriptive research utilizing secondary data derived from financial statements and annual reports of property and real estate sector companies listed on the IDX during 2018–2022. The sample used in this study consists of 168 companies, which were analyzed using IBM SPSS Statistics 25. The results of this study indicate that auditor switching significantly and positively influences audit quality. This suggests that auditor switching serves as a mechanism to maintain a less tight relationship between clients and auditors, thereby preserving auditor independence and ultimately enhancing audit quality. Conversely, audit tenure and audit firm size do not significantly affect audit quality.